The complement system in Aspergillus fumigatus infections and its crosstalk with pentraxins. Issue 16 (12th February 2020) - Parente, Raffaella; Doni, Andrea; Bottazzi, Barbara; Garlanda, Cecilia; Inforzato, Antonio
Abstract : Aspergillosis is a life‐threatening infection mostly affecting immunocompromised individuals and primarily caused by the saprophytic fungus Aspergillus fumigatus . At the host–pathogen interface, both cellular and humoral components of the innate immune system are increasingly acknowledged as essential players in the recognition and disposal of this opportunistic mold. Fundamental hereof is the contribution of the complement system, which deploys all three activation pathways in the battle against A. fumigatus, and functionally cooperates with other soluble pattern recognition molecules, including pentraxins. In particular, preclinical and clinical observations point to the long pentraxin PTX3 as a nonredundant and complement‐dependent effector with protective functions against A. fumigatus . Based on past and current literature, here we discuss how the complement participates in the immune response to this fungal pathogen, and illustrate its crosstalk with the pentraxins, with a focus on PTX3. Emphasis is placed on the molecular mechanisms underlying such processes, the genetic evidence from human epidemiology, and the translational potential of the currently available knowledge. Abstract :